P-309 Endometriosis does not compromise early embryonic development as well as live birth: a retrospective analysis of 716 standard in vitro fertilization cycles. (30th June 2022) - Borini, A; Dell' Aquila, M; Bartolacci, A; Intra, G; Parodi, F; Patria, G; Zacà, C; Borini, E; Coticchio, G
Abstract: Study question: Does endometriosis compromise early embryonic development and/or clinical outcome in standard in vitro fertilization (sIVF) cycles? Summary answer: Endometriosis does not compromise embryo development or clinical outcome in sIVF cycles characterised by normal semen parameters. What is known already: IVF is an elective approach to overcome endometriosis-related infertility. The notion that IVF outcomes are altered in women with endometriosis the is scarce and conflicting. Different meta-analyses reached diverging conclusions concerning a possible impact of endometriosis on clinical outcome. With reference to laboratory outcomes, a reduced fertilization rate with sIVF was observed in several but not all studies. Study design, size, duration: A retrospective analysis of 716 women undergoing their first sIVF cycles from 2015 to February 2021, 205 with in situ endometrioma (class IV) and 511 with tubal factor infertility. Participants/materials, setting, methods: Diagnosis of endometriosis was based on ultrasound observation of cysts on at least two occasions at least two menstrual cycles apart. Women carrying atypical lesions, i.e., cysts with sonographic appearance compatible but not distinctive for endometriosis, were excluded. Multivariate analysis was conducted using the generalized estimating equation (GEE) approach, thus making it possible the analysis of variables with non-normal distribution. The primary study outcome was live birth rate. Main results and the role of chance: After adjustment for maternal, paternal age, maternal body mass index (BMI), anti-mullerian hormone (AMH) and follicle stimulating hormone (FSH) we found no significant difference in fertilization rate [78, 69 ± 26, 16 (Endo) Vs 79, 5 ± 24, 01 (Tubal)], embryo quality [33, 33 (0 – 57, 86) endometriosis vs. 33, 40 (0 – 67, 70) tubal factor], blastulation rate [52, 00 ± 15, 01 (endometriosis) vs. 55, 49 ± 14, 98 (tubal factor)], top quality blastocyst [38, 15 ± 18, 67 (endometriosis) vs. 34, 62 ± 14, 77 (tubal factor)], ongoing pregnancy [OR = 0, 84, 95% CI (0, 54 – 1, 32)], live birth [OR = 0, 89, 95% CI (0, 53 – 1, 48)], and miscarriage rate [OR = 0, 68, 95% CI (0, 27 – 1, 74)]. The only significantly different outcome was the percentage of embryos with ≥ 8 blastomeres on day 3 [25, 00 (0 - 60, 00) endometriosis Vs 40, 00 (0 - 67, 00) tubal factor]. Limitations, reasons for caution: The retrospective design of the study and lack of data on cumulative live birth rates are additional limitations. Wider implications of the findings: The results of our study suggest that in women with endometriosis fertilization rate, embryo quality, blastulation rate and live birth rate are not affected in sIVF cycles. Trial registration number: N.A.